Impacts of low concentrations of nanoplastics on leaf litter decomposition and food quality for detritivores in streams - Sahadevan, Seena (2022)
In forested streams, leaf litter decomposition is a vital ecosystem process, governed primarily by aquatic hyphomycetes. These fungi are crucial mediators of nutrients and energy to invertebrates and higher trophic levels. Very little information is available on the impact of low concentrations of different sizes of nanoplastic particles (NPPs) on leaf litter decomposition and aquatic hyphomycetes communities. Besides, NPPs impact on leaf litter nutritional quality and invertebrate feeding behaviour is unknown. We conducted a microcosm assay with varying concentrations (0-25 μg L-1) of small (100 nm; SNPPs) and large (1000 nm; LNPPs) plastic particles to assess their impact on leaf litter decomposition, sporulation rates and community structure of aquatic hyphomycetes. Furthermore, leaf litter was retrieved and fed to invertebrates to assess feeding rates. Our results indicated that leaf litter decomposition, fungal sporulation and abundance were significantly affected by NPPs concentrations and sizes. By contrast, leaf litter nutritional quality was impacted only by sizes. The NPPs, particularly SNPPs, augmented leaf litter polyunsaturated fatty acids (18-31%), consequently improving food quality; however, invertebrates' feeding rates were not impacted. Overall, our study provides novel insights on the risks posed by NPPs with pronounced impact at the basal trophic level.